2021
DOI: 10.3390/ijerph182212203
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status among Migrants from Middle- and Low-Income Countries to Europe: A Systematic Review

Abstract: Introduction. Economic inequality, political instability and globalization have contributed to the constant growth of the migration phenomenon in recent years. In particular, a total of 4.2 million people migrated to Europe during 2019 and most of them settled in Germany, France and Italy. Objectives. The objective of this study was to conduct a systematic review of studies analyzing the oral health condition among migrants from middle- and low-income countries to Europe and assessing the eventual association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…The study reports a high prevalence of dental abnormalities and infections, a public health issue that is often neglected in studies of migrant health. A review of studies analyzing the oral health status of migrants from middle-income and low-income countries to Europe reported a high prevalence of caries experience and lack of dental health in the host countries ( 22 ). A recent study has been conducted in France in a health center offering dental consults to migrants ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study reports a high prevalence of dental abnormalities and infections, a public health issue that is often neglected in studies of migrant health. A review of studies analyzing the oral health status of migrants from middle-income and low-income countries to Europe reported a high prevalence of caries experience and lack of dental health in the host countries ( 22 ). A recent study has been conducted in France in a health center offering dental consults to migrants ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the literature has shown that the oral health of the immigrant population is worse than that of the native population worldwide [ 17 , 33 ]. Numerous studies [ 4 , 6 , 19 , 22 , 23 , 24 ] have evaluated the oral health of immigrant populations residing in Spain with respect to native populations.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of existing studies on the relationship between socioeconomic status and periodontal disease are cross‐sectional. Between 2005 and 2022, eight review articles were published on this topic: Klinge and Norlund, 4 Boillot et al, 5 Borrell and Crawford, 6 Schuch et al 7 Bastos et al, 8 Singh et al, 9 Tadakamadla et al, 10 and Lauritano et al 11 The review by Boillot et al was a meta‐analysis on 18 studies. The authors found a pooled odds ratio of 1.86 ( P < .001) for the effect of low socioeconomic status on adverse periodontal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review, by Tadakamadla et al, 10 evaluated the effect of parental socioeconomic indicators (education, income, and occupation) on the periodontal status of children and adolescents. The systematic review by Lauritano et al 11 reviewed studies about the association of socioeconomic status with different aspects of oral health, including periodontal health among migrants from middle‑ and low‐income countries to Europe. All of the aforementioned reviews concluded that low socioeconomic status was associated with an adverse periodontal status.…”
Section: Introductionmentioning
confidence: 99%